Control authorities of internal affairs bodies in the sphere of drug trafficking - Шевчук, О. М. (Problems of legality, 2014)
The article deals with control authorities of internal Affairs bodies in the sphere of turnover of narcotic drugs, psychotropic substances and precursors. Established the concept of the legal status of the Management of the fight against illegal circulation of drugs of the Ministry of interior of Ukraine and describes its features. The classification of control authorities of internal Affairs bodies in the sphere of turnover of narcotic drugs, psychotropic substances and precursors and analyzed for their content.